Overview of Personal Hygiene Knowledge Level with the Prevalence of Vaginal Discharge in Students of Premedical School Udayana University - Adiwati, Erica Luis; Kwartantaya, Ketut; Darmaputra, I Gusti Nyoman; Saraswati Sudarsa, Prima Sanjiwani (E-Jurnal Medika Udayana; Vol 14 No 01 (2025): E-Jurnal Medika Udayana, 2025)
Personal hygiene is the practice of keeping oneself clean that can prevent people from various diseases brought on by poor sanitation. This is related to the occurrence of vaginal discharge, which is the white fluid that usually comes out of the vagina after women enter the puberty phase. This study was conducted to find out an overview of the level of personal hygiene knowledge of students of the Bachelor of Medicine Study Program, Faculty of Medicine, Udayana University with the prevalence of vaginal discharge. Data for this study is collected through a cross-sectional descriptive method. The consecutive sampling technique was used to select the research sample which consisted of 124 students of the Bachelor of Medicine Study Program, Faculty of Medicine, Udayana University. Based on the research, 117 respondents (94.4%) had good knowledge, 7 respondents (5.6%) had sufficient knowledge, and none had a bad level of knowledge. Overall, the overview of the level of personal hygiene knowledge of students of the Bachelor of Medicine Study Program, Faculty of Medicine, Udayana University with the incidents of vaginal discharge, is mostly in the good category. The most widely used source of information is the mass media, therefore it is necessary to improve and control the quality of information.